1981
DOI: 10.1159/000156015
|View full text |Cite
|
Sign up to set email alerts
|

The Karyotype of Cacajao melanocephalus (Platyrrhini, Primates)

Abstract: Chromosome studies were performed in a male representative of Cacajao melanocephalus. The diploid number was 45: the chromosome complement consisting of 12 pairs of acrocentric autosomes, 9 pairs of biarmed autosomes and 1 heteromorphic pair composed of one subtelocentric and one acrocentric chromosome. The X chromosome was submetacentric and the Y chromosome was apparently translocated to an acrocentric autosome. G-banding patterns were studied and the results compared to karyotypes previously described for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Cytogenetic studies have shown that New World primates are karyologically diverse, and some species are highly derived with respect to the chromosome complement of humans or a presumed platyrrhine ancestor (Chu and Bender 1962;Koiffmann and Saldanha 1981;Consigliere et al 1996Consigliere et al , 1998Stanyon et al 2000;Bonvicino et al 2003). The genus Callicebus is one of the best examples of this diversity because diploid numbers among species range from 2n=50 (Rodrigues et al 2001) to 2n=16 (Bonvicino et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic studies have shown that New World primates are karyologically diverse, and some species are highly derived with respect to the chromosome complement of humans or a presumed platyrrhine ancestor (Chu and Bender 1962;Koiffmann and Saldanha 1981;Consigliere et al 1996Consigliere et al , 1998Stanyon et al 2000;Bonvicino et al 2003). The genus Callicebus is one of the best examples of this diversity because diploid numbers among species range from 2n=50 (Rodrigues et al 2001) to 2n=16 (Bonvicino et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In most of these animals however, the aberration was a Y chromosome translocated to an autosome. Translocation involving Y chromosomes has been found in Alouatta palliata [Ma et al, 1975], Alouatta fusca clamitans [Koiffmann and Saldanha, 1974], Cacajao melanocephalus [Koiffmann and Saldanha, 1981], Callimico goeldii [Hsu and Hampton, 1970] and Aotus trivirgatus [Ma et al, 1976a]. In the latter species, extensive karyotypic polymorphism has been described [Brumback, 1974], In cytogenetic studies of A. trivirga tus from 4 different South American countries, Ma et al [1976b] identified 7 distinctive karyotypes among 330 individuals belonging to four distin guishable pelage phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In C. melanocephalus 2n = 45 for males and 46 for females, with 12 acrocentric pairs, 9 biarmed pairs, 1 heteromorphic pair, a submetacentric X chromosome, and a Y chromosome that has translocated to an acrocentric autosome (Koiffman and Saldanha 1981). Robertsonian translocations have occurred during evolution; C. calvus and C. melanocephalus have acquired 1 translocation since their divergence (Veigas-Pequignot et al 1985).…”
Section: --Cacajao Melanocephalusmentioning
confidence: 99%